The adolescent health and youth development program a strategic plan - Lilam, Gilda L. (U.P. in Mindanao, 2001)
The population programs for General Santos City are anchored in the Commission on Population which is the lead agency and coordinator of the Philippine Population Management Program where the Adolescent Health and Youth Development Program is a major program component.